Memory and knowledge of the sea in Southeast Asia - Wong, Danny Tze-Ken (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2008)
In the Southeast Asian region, various communities have been closely associated with the sea. Many have, over the years, acquired special memory and, sometimes, intimate knowledge of the sea. Even as much of this information and knowledge was passed from generation to generation, it provided maritime communities with a sense of identity and social cohesiveness as well as a sense of belonging. It was in this light that the papers in this volume set out to investigate the human association with the sea in Southeast Asia through the interrogation of memory and knowledge preserved through various genres including oral tradition, travellers' tales and diaries, official accounts as well as rituals.